Perception sociale de la crue et réponse des pêcheurs à la baisse de l’inondation des plaines dans le Delta Intérieur du Niger, Mali - Sévère Fossi; Bruno Barbier; Yao Télesphore Brou; Amaga Kodio; Gil Mahé (Territoire en Mouvement, 2012)
The drought that prevails in the Sahel since the seventies has significantly reduced the production in all sectors. In the Inner Niger Delta in Mali (DIN), fishing whose development is closely linked with the inter-seasonal and inter-annual fluctuations of the flood of the River Niger, is still in a deep crisis. Catches have declined by half, many fishermen left, some have adopted unsustainable practices and social rules are collapsing. The results obtained show that fishermen have an accurate perception of the flood and its evolution along the time. The total annual catch has dropped considerably and almost all fishermen agree that this decline is related not only to the amount collected, but also to the quality of the catches. Accordingly, 40 % of the fishermen relegated fishing to the row of ancillary activity and 35 % diversified their activities into agriculture, trade or transport. However, few fishermen of DIN imagine their lives under conditions of profound changes of the flood of the river Niger.